مظاهرُ الصِّدِّيقية في إنجازاتِ الخليفة أبي بكرٍ رضي الله عنه - شرفه, حسين (University of Eloued جامعة الوادي, 2017)
يتناول هذا البحث جانبا من جوانب التميُّز في شخصية الخليفة أبي بكر رضي الله عنه ممثلا في الصِّدِيقية، وهي الصفة التي فاق بها الصحابة رضي الله عنهم، وحاز بها لقب الصِّدِيق في هذه الأمة، وستحاول هذه الدراسة إبراز حقيقة تلك المنقبة من خلال الإنجازات التي حققها في خلافته. وإذا كانت خلافة الصِّدِيق رضي الله عنه لم تدم طويلا- إذ لم تزد عن سنتين وثلاثة أشهر- فإنها شهدت أربعة إنجازات كبيرة قلما تكررت في التاريخ، وليس لها من تفسير سوى ما حظي به الخليفة أبوبكر رضي الله عنه من مناقب وفضائل، خاصة صديقيته التي أهلته أن يقود المسلمين بعد وفاة النبي صلى الله عليه وسلم. فما حقيقة الصِّدِيقية؟ وكيف تجلت مظاهرها في إنجازات الخليفة أبي بكر رضي الله عنه؟ ذلك ما تروم هذه الدراسة بيانه .. وبالله التوفيق والسداد. This investigation deals with an aspect of excellence in the personality of the Caliph Abu Bakr, may Allah be pleased with him represented in Alsidikiah i.e the most truthful. This latter is the capacity in which he exceeded his companions, God bless them, and he won the title of the most righteous in this nation. This study attempts to highlight the reality of this virtue through the achievements he realized during his succession. Although the succession of the faithful person lasted no more than two years and three months, it had witnessed four great achievements rarely repeated in history. This has no other explanation other than the qualities and virtues endowed to the Caliph Abu Bakr, may Allah be pleased with him especially his faithfulness, which qualified him to lead the Muslims after the death of the Prophet, peace be upon him. So, what is the truth behind the truthfulness of Abu Bakr, may Allah be pleased with him? And how its aspects have been manifested in his succession
The aspects of truthfulness of Abu Bakr
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: أبوبكر الصديق- الخلافة- القيادة- التميّز; Abu Bakr Siddiq - khilafa - Leadership - Excellence